Amido de trigo mourisco (Fagopyrum esculentum): obtenção, modificação por tratamento com calor e baixa umidade e caracterização - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
Buckwheat (Fagopyrum esculentum) is a pseudoceral, its grains are nutritionally rich and boast great technological potential for use in the food industry as an ingredient of functional products, flour is considered a an alternative to celiacs because it does not contain gluten. The buckwheat starch granules have a spherical or polygonal shape, with an average size of 2- 14 μm, as well as physico-chemical, structural and thermal properties that facilitate industrial applications. Starches in their native form have restricted use in the industry and for this reason modifications are made to increase their application. The present work had the objective of extracting buckwheat starch, physical-chemical and technological properties evaluation, modification by heat treatment in low moiture and evaluation of the effect of the different contents of moisture used in this modification. To evaluate the morphology of the granules, analysis was performed by means of electron microscopy. Color change after heat treatment was checked by color determination analysis. The thermal properties of the native and modified starches were analyzed by means of Thermogravimetry and Differential Scanning Calorimetry. X-ray diffraction and spectroscopy in the Fourier transform infrared region were performed to evaluate the structural properties of the starches and the pulp property was analyzed using the Rapid Visco-Analyzer equipment. The results showed that there was no significant difference in the polygonal / spherical shape and the diameter of the granules, nor was there any significant difference in X-ray diffraction and spectral bands. There was a difference in the staining of the modified starches in relation to the native, in the same manner as in relation to the thermal properties differences in the thermal stability after modification and in the gelatinization temperature of the modified starches in relation to the native starch were observed. There was a change in the pulp properties of the modified starches. Changes in the technological characteristics of buckwheat starch are considered, preserving the initial structure.
Keywords: Análise térmica; amido; modificação física; Fagopyrum esculentum; RVA; DSC; Thermal analysis; starch; physical modification; Fagopyrum esculentum; RVA; DSC; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS